2011
DOI: 10.1152/ajpendo.00709.2010
|View full text |Cite
|
Sign up to set email alerts
|

NOD1 activation induces proinflammatory gene expression and insulin resistance in 3T3-L1 adipocytes

Abstract: Chronic inflammation is associated with obesity and insulin resistance; however, the underlying mechanisms are not fully understood. Pattern recognition receptors Toll-like receptors and nucleotide-oligomerization domain-containing proteins play critical roles in innate immune response. Here, we report that activation of nucleotide binding oligomerization domain-containing protein-1 (NOD1) in adipocytes induces proinflammatory response and impairs insulin signaling and insulin-induced glucose uptake. NOD1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
66
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 51 publications
2
66
0
1
Order By: Relevance
“…In the current issue, Zhao et al (14) demonstrate that administration of a PGN-based NOD1 activator to adipocytes activates inflammatory programs, impairs insulin signaling, and decreases insulin-stimulated glucose uptake. That paper also shows that human primary adipocytes respond to NOD1 ligand by inducing expression of inflammatory mediators.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In the current issue, Zhao et al (14) demonstrate that administration of a PGN-based NOD1 activator to adipocytes activates inflammatory programs, impairs insulin signaling, and decreases insulin-stimulated glucose uptake. That paper also shows that human primary adipocytes respond to NOD1 ligand by inducing expression of inflammatory mediators.…”
mentioning
confidence: 94%
“…Interestingly, Zhao et al (14) suggest that multiple levels of regulation for NOD1-mediated sensing of PGN may take place during obesity, since NOD1 transcripts were higher in epididymal adipose tissue of mice after high-fat feeding. It will be important to ascertain if circulating or tissue resident NOD ligands, potentially derived from gut flora, are altered during obesity and if these factors are necessary and/or sufficient to induce insulin resistance.…”
mentioning
confidence: 99%
“…Their activation, by bacterial peptidoglycans, results in nuclear factor kB (NFkB)-induced gene transcription. Recently, NOD1 and NOD2 have been shown to play an important role in inflammation and insulin resistance in adipocytes (Winzer et al 2004, Yi-Jun et al 2012, Zhao et al 2011, Zhou et al 2012, Purohit et al 2013. The levels of NOD1 and NOD2 mRNA are markedly increased in differentiated murine 3T3-L1 adipocytes and human primary adipocyte cultures upon adipocyte conversion.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of NOD1 and NOD2 mRNA are markedly increased in differentiated murine 3T3-L1 adipocytes and human primary adipocyte cultures upon adipocyte conversion. Moreover, Nod1 mRNA is markedly increased only in the fat tissues of diet-induced obese mice (Zhao et al 2011). The Nod1/2 knockout mice are protected from high-fat-diet-induced inflammation, lipid accumulation and peripheral insulin intolerance (Schertzer et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…NOD1 and NOD2 induce the recruitment of receptor-interacting serine/threonine-protein kinase 2 (RIP2), which promotes NF-κB-mediated proinflammatory gene expression when exposed to signal molecules (25). Previous research showed that activation of NOD1 or NOD2 contributes to insulin resistance and a proinflammatory response (26)(27)(28). On this basis, the current study explored the relationship between resistin and NOD receptors.…”
Section: Introductionmentioning
confidence: 97%